2021
DOI: 10.3390/jcm10215025
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Early Intervention Sessions and Vocabulary Skills in Children with Hearing Loss

Abstract: Background: A primary goal of early intervention is to assist children in achieving age-appropriate language skills. The amount of intervention a child receives is ideally based on his or her individual needs, yet it is unclear if language ability impacts amount of intervention and/or if an increased frequency of intervention sessions results in better outcomes. The purpose of this study was to determine the relationship between the frequency of early intervention sessions and vocabulary outcomes in young chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
2
16
1
Order By: Relevance
“…However, children who enroll at later ages may be entering EI with more delayed developmental outcomes and therefore require more intense services (more time in service and more service types) to try and “catch up” prior to EI exit that is required at 36 months of age. Consistent with a previous work [ 12 ], we found that children with either bilateral or more significant degrees of hearing loss had levels of higher service intensity. Children with more severe levels of hearing loss may require additional services, given the potential greater impact their hearing loss may have on language development, compared to those with milder levels.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, children who enroll at later ages may be entering EI with more delayed developmental outcomes and therefore require more intense services (more time in service and more service types) to try and “catch up” prior to EI exit that is required at 36 months of age. Consistent with a previous work [ 12 ], we found that children with either bilateral or more significant degrees of hearing loss had levels of higher service intensity. Children with more severe levels of hearing loss may require additional services, given the potential greater impact their hearing loss may have on language development, compared to those with milder levels.…”
Section: Discussionsupporting
confidence: 92%
“…Previous literature has stated that children enrolled in EI receive a range of service intensity from approximately 2 h per week [ 18 ] to 2–3 h per month [ 19 , 20 , 21 ]. Wiggen et al [ 12 ] reported that children who were DHH received on average 3–4 intervention sessions per month ranging from 30–90 min, with the majority of sessions lasting 60 min each. Intervention sessions were not necessarily limited to Part C EI and included sessions that occurred within intervention centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among intervention variables predicting language outcomes early fitting with hearing aids and/or early cochlear implantation and timely access to family-centred early intervention as well as a higher intensity of early intervention haven been shown to predict language and functional communication outcomes [ 17 , 36 , 37 , 38 ]. International consensus based best practice of family-centred early intervention has been described and is supported by growing empirical evidence [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Self-efficacy in fathers was shown to be related to higher involvement and perceived support from EI providers, emphasizing efforts to actively increase involvement of fathers. In a multicenter longitudinal North American study Wiggin et al [ 10 ] investigated effects of increased frequency of early intervention sessions in children 9 to 36 months of age. By structural equation modeling controlling for maternal education, degree of hearing loss and meeting with the Joint committee on Infant Hearing 1-3-6 guidelines (completion of screening by 1 month, diagnosis of hearing loss by 3 months and enrolment in intervention by 6 months of age) significant effects of a higher number of intervention sessions at the first assessment on expressive vocabulary outcomes 9 months later was found.…”
mentioning
confidence: 99%